Fiber Bragg Grating and Channel Spacing Effect in WDM Radio over Fiber System Using DPSK Modulation Format - Ahmed Mahmood, Hussein; Khlf Ahmed, Riyadh (International Journal of Engineering and Technology, 2018)
Fiber Bragg Grating (FBG) is distributed reflector written in short length of optical fiber to reflect specific wavelengths of light and transmit the other components of spectra. By using FBG method in dispersion compensation can boost significantly the system performance. High capacity transmission and low effective cost of Radio over Fiber technique (Rof) are resulted from the combination of the optical communication capacity and the mobility of wireless networks. In this research article, an investigation of radio over fiber transmission for 50 km-long optical fiber operated at 10 Gb/s data rate and modulated under efficient DPSK modulation technique. The effect of Fiber Bragg Grating as chromatic dispersion compensation and channel spacing in WDM on optical communication system is analyzed and evaluated. The system performance is evaluated in terms of eye diagram. The outcomes of our simulation shows that Four unequal spacing channels radio over fiber system with ideal dispersion FBG has the best performance in terms of Q-factor and BER.Â Â